Establishment of the hairy root culture of Echium plantagineum L. and its shikonin production - Fu, Jiang-Yan (3 Biotech, 2020)
Echium plantagineum L. (Boraginaceae) is an invasive species in Australia and contains medicinal shikonins in its roots. In this study, the hairy root lines of E. plantagineum were established using Agrobacterium rhizogenes strain ATCC15834 and confirmed by the amplification of the rolB gene. Results showed significant difference in shikonin production between the hairy root lines in the (1)/(2)B5 and M9 media. The biomass of the lines in the (1)/(2)B5 medium was fivefold of that in the M9 medium. However, the components of detected shikonins were similar in these two liquid media. By contrast, different accumulation profiles appeared in the hairy root lines. HPLC analysis revealed the presence of nine possible related compounds, including shikonins, and acetylshikonin was the most abundant shikonin derivative. The content of acetylshikonin in the (1)/(2)B5 medium (36.25 mg/L on average) was twofold of that in the M9 medium. Our results showed that the hairy root cultures of E. plantagineum can be used in enhancing the production of potential pharmaceutical compounds, such as acetylshikonin.